2013
DOI: 10.1016/j.chembiol.2012.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Wall Teichoic Acid Inhibitors as Potential Anti-MRSA β-Lactam Combination Agents

Abstract: Summary Innovative strategies are needed to combat drug resistance associated with methicillin-resistant Staphylococcus aureus (MRSA). Here, we investigate the potential of wall teichoic acid (WTA) biosynthesis inhibitors as combination agents to restore β-lactam efficacy against MRSA. Performing a whole cell pathway-based screen we identified a series of WTA inhibitors (WTAIs) targeting the WTA transporter protein, TarG. Whole genome sequencing of WTAI resistant isolates across two methicillin-resistant Staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
156
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(163 citation statements)
references
References 44 publications
(114 reference statements)
5
156
0
2
Order By: Relevance
“…Since the TarG inhibitory effect of L275, L638, L640 and L555 could not be fully suppressed, it is likely that these compounds display an off-target associated non-specific cellular toxicity or even address secondary targets. (Wang et al 2013) The frequencies of resistance development for compounds L275 22 at 8x MIC) and L638 25 (FOR 1.9 x10 -10 at 8x MIC) were significantly lower than for targocil. Beyond tunicamycin A 28, which displayed selective inhibitory activity for TarO in bacteria, but was cytotoxic for eukaryotic cells due to a promiscuous inhibition of UDP-HexNAc:polyprenol-P HexNAc-1-P family of enzymes including GlcNAc phosphotransferase (Swoboda et al 2011), the first early-stage WTA biosynthesis inhibitor reported was ticlopidine 29.…”
Section: Lessons Learned From Druggable Targets In Bacteriamentioning
confidence: 93%
See 3 more Smart Citations
“…Since the TarG inhibitory effect of L275, L638, L640 and L555 could not be fully suppressed, it is likely that these compounds display an off-target associated non-specific cellular toxicity or even address secondary targets. (Wang et al 2013) The frequencies of resistance development for compounds L275 22 at 8x MIC) and L638 25 (FOR 1.9 x10 -10 at 8x MIC) were significantly lower than for targocil. Beyond tunicamycin A 28, which displayed selective inhibitory activity for TarO in bacteria, but was cytotoxic for eukaryotic cells due to a promiscuous inhibition of UDP-HexNAc:polyprenol-P HexNAc-1-P family of enzymes including GlcNAc phosphotransferase (Swoboda et al 2011), the first early-stage WTA biosynthesis inhibitor reported was ticlopidine 29.…”
Section: Lessons Learned From Druggable Targets In Bacteriamentioning
confidence: 93%
“…Early stage WTA inhibition can lead to cells showing enhanced sensitivity to certain drugs (see next chapter) (Sewell and Brown 2014;Lee et al 2016a). In contrast, late stage inhibition of membrane-bound WTA precursors is lethal due to accumulation of toxic intermediates and the depletion of cellular pools of bactoprenol phosphate D Elia et al 2006b; Swoboda et al 2011;Brown et al 2013;Wang et al 2013), which is essential for peptidoglycan biosynthesis as discussed above. Furthermore, it is known that teichoic acids anchor autolysins to prevent uncontrolled hydrolysis of peptidoglycan (Bierbaum and Sahl 1985;Dubée et al 2011).…”
Section: Lessons Learned From Druggable Targets In Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…For example, forward genetics platforms such as the S. cerevisiae haploinsufficiency profiling (HOP) (Shoemaker et al 1996;Giaever et al 1999Giaever et al , 2002Giaever et al , 2004Roemer et al 2011a) or C. albicans fitness test (Xu et al 2007;Jiang et al 2008;Roemer et al 2011b) offer whole cell target-specific assays for essentially all possible drug targets in yeast and has proven enormously successful in the discovery and mechanism of action (MOA) determination of novel antifungal agents (Roemer et al 2011a(Roemer et al , 2012. As routinely performed in antibacterial discovery Roemer and Boone 2013;Wang et al 2013), next-generation sequencing also offers greater speed and resolution in determining the MOA of potential antifungal leads. Whole genomes of drug-resistant mutants derived from haploid S. cerevisiae, C. glabrata, C. neoformans, or newly derived haploid C. albicans strains (Hickman et al 2013), and even A. fumigatus are now (or soon to be) routinely sequenced to map causal mutations, thereby definitively identifying the drug target by genetic means.…”
Section: Future Directionsmentioning
confidence: 99%